Development of Digital Learning Materials Using a QR Code Based Book Creator Application to Improve Student Learning Outcomes in Science Subjects - Widanti, Adima Putri; Fathurrahman, Moh. (Postgraduate, University of Mataram, 2024)
This research aims to develop digital learning material using the QR Code-based Book Creator application to improve learning outcomes in science, especially on human digestive system material. This research uses the ADDIE development model. The results showed that the use of digital learning material using the QR Code-based Book Creator application was able to improve student learning outcomes as evidenced by an increase in the gain value of 0.39 in small groups and 0.54 in large groups with moderate categories. In addition, this digital learning material is also considered very feasible by experts with a feasibility score of 98.60% from media experts and 93% from material experts. Positive responses also came from teacher with a response questionnaire score of 95% and a student response score of 93.30% with very feasible criteria for use in learning the human digestive system. Based on these results, the digital learning material developed not only improves student learning outcomes on human digestive system material but the learning material is very feasible to use.